Kompleksitas Penegakkan Hukum Ekonomi Di Era Reformasi - Anto Kustanto (SOSIO DIALEKTIKA : JURNAL ILMU SOSIAL HUMANIORA, 2021)
Issues that are understood about law relating to the nature of law are made to regulate the order of people's lives so that they are orderly and regularly. Order and regular will not be realized if the rule of law cannot be enforced. The implications of legal regulation in the economic field are various regulatory instruments that affect economic performance, in order to achieve human welfare, both in the short and long term. In this case, the law position is trying to provide a reflection for the creation of an economic justice. Awareness of the need to understand the economic consequences of implementing a rule has actually begun to be discussed, so from this illustration it becomes an argument about the Complexity of Enforcement of Economic Law in the Reformation Era. The aim is to reveal the meaning of a legal action based on law enforcement in the economic field as well as to identify the relationship between variables. Thus, this research produces descriptive data which must be interpreted using qualitative methods. Because this article seeks to provide an explanation of the continuity and integrity of the science and philosophy of law. The reasons that underlie industrial countries and developing countries such as Indonesia, regard the enforcement of economic law as very important, namely program effectiveness, reasons for justice, reasons for credibility, and reasons for efficiency. The phenomenon of economic instability in the reform era is a reflection that management in the economic sector has not fully become our collective commitment, a reductionist and exploitative way of thinking has developed to color the administration of government in the reform era. Enforcement of economic law is actually a preventive or repressive effort in overcoming price volatility and market mechanisms. Law enforcement as a concept that is expected to be one of the foundations for achieving Indonesia's vision in 2030, economic law enforcement occupies an important position to be prioritized because of the vital functions it contains. This concept is an interface between the legal system and the economic system in an effort to realize legal and economic development as a series of stages of nation building. The development of economic law, enforcement in the reform era that its implications for legal institutions and the legal profession. Therefore, it is a challenge for the Indonesian nation in the reform era to find a solution in addition to the challenges of the legal profession, economic actors, and other related professions. In meeting these challenges, an attitude that we need to develop together is openness and “intellectual humility”, realizing that we will be more successful in making contributions if we work together in an interdisciplinary manner.